P-88 Dementia pathway – from diagnosis to end of life. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Lipscombe, Erika; Hanson, Emma
Abstract : The City Council invited local charities to tender to provide services that would contribute to sustaining and improving dementia diagnosis rates and enable the city to become a dementia friendly city. Three charities came together and were successful in demonstrating how they would work in partnership to support a person with dementia from diagnosis to end of life working alongside statutory provision. The key objective for the new service was to support the person diagnosed with dementia and their carers through the allocation of a named 'contact' facilitating people and their carers to access and use services. The hospice in partnership with the service employs two Clinical Nurse Specialists (CNSs) who lead the complex dementia and end of life care support pathway aspect. Referrals are via a single point of access, including self-referrals and are prioritised according to a 'RAG' system leading to either 'social' support or the support of a CNS. Support for patients with dementia and their carer is through a 'drop in' service where they can meet a member of the team, also through carer support groups, activity groups and training for carers. A Saturday morning coffee group has been set up to support those carers who work in the week and cannot attend week-day events; the service is now working later in the evenings. Clients are supported to remain in their preferred place for care and following death bereavement support is provided. The service reports through KPIs to the Council; the two CNSs have seen 180 patients with complex dementia, and have supported 40 people with dementia to die within their 'preferred' place of care, working alongside the carers pre- and post- bereavement. An interesting observation is that the numbers of those people with dementia needing in-patient care through the hospice has not increased.